Perancangan Model Pembangkit Listrik Dengan Menggunakan Teknologi Pompa Tanpa Motor (Hydraulic Ram Pump) - Jorfri Boike Sinaga; Azhar Azhar; Novri Tanti; Sugiman Sugiman (JURNAL MECHANICAL, 2017)
This paper presents the design of parameters of  hydraulic ram pump and hydraulic turbine to use  the energy of flowing water for water supply to generate electrical power and irrigation. Design of  parameters of hydraulic ram pump with head of water supply of 1,5 m was obtained: 1,25 in. diameter and  8 m length of drive pipe,  200 gr and 4,6 cm of weight  and diameter of impulse valve,  4.200 cm3 of air chamber volume. The testing results of the hydraulic ram pump model shown that water could be pumped as far as the height of 7 m and 8 m, with the volume flow rate of 2,755 lit/men and 1,73 lit/men.  Design of  geometric parameters of cross flow hydraulic turbine with head of water supply of 1,75 m was obtained:  12 cm and 8 cm of external and internal diameter, 25 cm of runner width,  and 18 of runner number.   The testing results of the cross flow hydraulic turbine shown that power could be generated 83,47 W with the volume flow rate of 0,01 lit/s and the efficiency of 71,05 % at 799 rpm. The testing result also shown that with using volume flow rate of 0,003 lit/s, this turbine could be generated 23,39 W with the efficiency of 46,64 %. Technically the technology of hydraulic ram pump can be developped and used to supply of water for irrigation and generating of electrical power.